Microdosimetric modeling of the sensitometric curve of GafChromic films in the photon fields. (January 2020) - Moslehi, A.; Ansari, M.; Monadi, Sh.
Highlights: Calibration curve of EBT3 GafChromic film is experimentally measured. The calibration curve is calculated by the microdosimetric one-hit detector model. The saturation parameters are determined by the single-event microdosimetric spectra. The calculated calibration curve is 11% different from the measurements in the worst case. Abstract: The sensitometric curve of EBT3 GafChromic film located at a depth 5 cm of RW3 water-equivalent phantom exposed to 6 MV X-rays is investigated. Variation of optical density for absorbed doses less than 2 Gy is determined by the experimental measurement together with the microdosimetric one-hit detector model. It is found that this model needs two fitting parameters, a maximum optical density and a saturation parameter. Both of them depend on the film structure as well as the photon spectrum. Meanwhile, the saturation parameter is a function of the microdosimetric single-event distribution of specific energy, i.e., f 1 ( z ) . To calculate this distribution, irradiation of the films is simulated by the Geant4 toolkit. A sample of EBT3 film with 2 mm × 2 mm area is simulated. Active layer of the film is considered to contain 5000 cylindrical sensitive targets (SV) with 9.4 μ m length and 1.62 μ m diameter, located in random positions with different axial directions. The results obtained show that below an absorbed dose 1 Gy the maximum difference between the measured and the calculated optical densities is about 11%, while for the doses above 1 Gy the discrepancy is at most 3%. Eventually, it can be concluded that the sensitometric curve of EBT3 GafChromic film can satisfactorily be determined by the microdosimetric one-hit detector model, especially in the dose range above 1 Gy.